AN EVALUATION FOR PREVENTING CROSS-HATCHED AREA VIOLATIONS ON HIGHWAYS - Dogan, Erinc Ezgi; Gursoy, Mustafa (YILDIZ TECHNICAL UNIV, 2017)
Cross-hatched (chevron markings or simply hatched are also terms used in the literature) areas on highways emphasize that these areas are not permitted to be used by vehicles and also provide information for changing flow direction and/or for merging or diverging different flows. Thus, these areas are also indicators of possible bottleneck sections. Violations at these sections at peak hours cause reduction in road capacity. Violations at off peak hours, on the other hand, cause serious risks of accidents especially on high-speed highway merging and diverging ramps. Some parts of our road network, both urban and intercity, can be monitored by traffic camera systems, and traffic fines can even be sent to drivers who violate the traffic rules. However, there is no quantitative evaluation of these violations or their frequency. In our study we demonstrated that violations made by mostly commercial vehicles and meaningful differences on violations between observed sections seen as well. In the study presented, comparative results with those of international literature are shared. This study was made with the help of Yildiz Technical University Traffic Control Centre Laboratory working in coordination with the Istanbul Metropolitan Municipality (YTU-IBB-TKM-Lab). We believe the results of the study are sociologically worthy of evaluation.
Keywords: Traffic safety; hatched area; traffic violation; enforcement; Engineering